MicroRNA regulation of the proliferation and apoptosis of Leydig cells in diabetes - Li Hu; Shaochai Wei; Yuqi Wu; Shulin Li; Pei Zhu; Xiangwei Wang (BMC, 2021)
Abstract Background The number of patients with diabetes is increasing worldwide. Diabetic testicular damage can cause spermiogenesis disorders and sexual dysfunction. We thus explored the role of miRNAs in diabetic testicular damage, and revealed that they could serve as effective prevention and treatment therapeutic targets. Methods Streptozotocin (STZ) was used to generate a rat model of type 2 diabetes. Rat testicular tissues were used for miRNA and mRNA sequencing. Through bioinformatics analysis, we constructed an miRNA-mRNA diabetic testicular damage regulatory network and screened for key miRNAs. We also used Leydig cells to generate a diabetic cell model and detected the downstream target genes of miRNAs, secretion of testosterone, and proliferation and apoptotic levels to elucidate the role and mechanism of the selected miRNAs in diabetic testicular damage. Results Using second-generation sequencing, we identified 19 differentially expressed miRNAs and 555 mRNAs in the testes of diabetic rats. Based on computational prediction of targets and negative regulation relationships, we constructed a miRNA-mRNA regulatory network, including 12 miRNAs and 215 mRNAs. KEGG enrichment analysis revealed that genes were more concentrated on the survival signalling pathway. Based on this, we screened 2 key miRNAs, miR-504 and miR-935. In vitro, glucose could induce an increase in miR-504 and miR-935, whereas a decrease in MEK5 and MEF2C in a dose-dependent manner. Overexpression of miR-504 and miR-935 led to the decreased expression of MEK5 and MEF2C, decreased proliferation rate of Leydig cells, increased apoptotic rate, and decreased secretion of testosterone. Whereas, knockdown of miR-504 and miR-935 displayed opposite tendencies. Conclusions miRNAs play important roles in diabetic testicular damage. miR-504 and miR-935 might regulate testicular damage through the classic survival pathway of MEK5-ERK5-MEF2C. Targeted inhibition of miR-504 and miR-935 could reverse the high-glucose-induced testicular complications, thus posing as a potential therapeutic approach in diabetic testicular injury.